Vol. 3, No. 1, September 2021 - Aap Apipudin1; Yofy Syarkani (Scientia Regendi, 2021)
This study aims to determine the level of conformity between the expectations of inpatients and the quality of health services at Ciamis Hospital. To determine the effect of service quality on inpatient satisfaction at Ciamis Hospital. In line with the problems and research hypotheses, this research was carried out using a survey design, namely research that took a sample from one population and used a questionnaire as a means of collecting basic data. In this study, a sample of 100 patients was used. The sampling technique in this study used a proportional random sampling technique. Quantitative analysis in this study will use validity and reliability tests with Cronbach's Alpha. Classical assumption test includes heteroscedasticity test and normality test. To test the hypothesis using multiple linear regression. All tests used the SPSS 11.5 computer program. The results show that the overall service dimension, the suitability between the services provided by the Ciamis Hospital and the patient's expectations, there is a gap / level of satisfaction of (-0.36), this score is categorized in the medium group, although it has not fully met the patient's expectations but the services provided have been pretty good. Based on the results of the regression analysis above, it can be concluded that all variables from the dimensions of service quality (reliability, responsiveness, confidence, tangibles and empathy) together have a positive and significant influence on the satisfaction of inpatients at Ciamis Hospital. These results indicate that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, the biggest influence is the tangible variable (5.191) followed by responsiveness (4.280), reliability (4.059), empathy (1.989), and confidence (-4.205 ) on the satisfaction of inpatients at Ciamis Hospital. The result is R2 of (0.789) indicating that 78.9% of patient satisfaction variables can be explained by service quality, namely reliability, responsiveness, confidence, tangibles and empathy while the remaining 21.1% are explained by other variables that are not included in this research model.